VAGINAL MICROBIOTA COMPOSITION PROFILES IN WOMEN AT DIFFERENT LIFE STAGES - Krsteva, Nadica; Labachevska-Gjatovska, Liljana; Kostovski, Marko; Mihajlov, Kiril; Jovchevski, Radomir; Grdanoska, Tatjana; Kacarska, Aleksandra; Lameski, Maja (Journal of Morphological Sciences, 2024)
The vaginal microbiome is a reproductive organ-specific association that harbors a unique collection of anaerobic and aerobic microorganisms. It plays a crucial role in woman`s reproductive wellbeing and prevention of urogenital diseases including bacterial vaginosis (BV), infections with opportunistic microorganisms, yeast infections, urinary tract infections and sexually transmitted diseases. The composition of the vaginal microbiota undergoes significant changes during different stages of women's life cycle and is influenced by variations in sex hormone levels, physiological factors (e.g. the menstrual cycle and pregnancy) and individual lifestyle choices. Evidence shows that these various factors can influence the vaginal microbiome, potentially leading to an imbalance in the microbial community and genital infections. The aim of the present study was to compare the composition of vaginal microbiota in women at different life stages. A total of 2032 vaginal and cervical swab samples from women at different age, submitted for routine testing at the Institute for microbiology and parasitology were analyzed. Vaginal microbiota was evaluated by means of quantitative PCR in real time (Femoflor Screen, DNA-Technology).The results showed a dominance of lactobacilli in majority of the samples from the first two groups young women and women in reproductive years (72% and 69%, respectively), whilst a decrease of normocenosis was noted in women over 45 years (47%). Moderate dysbiosis was detected in 18% of both 15-25 yrs and 25-45 yrs age groups compared to 21% of the women of the > 45 yrs group. Severe dysbiosis prevailed among women of the >45 yrs group (32%) compared to 13% and 10% in the 15-25 yrs and 25-45 yrs age groups, accordingly. The results from this study provide comprehensive picture of our current knowledge of the composition and abundance of the microbiota of the female reproductive tract during different life phases. The tremendous importance of the microbiome for the reproductive health imply a necessity of future studies focused on  providing more detailed information its composition  and susceptibility to external influences. Keywords: vaginal microbiota, reproductive health, Lactobacillus..